Infection Control and Modified Workflow Strategies in Radiation Oncology Department during COVID 19 Crisis: An Institutional Experience - Sweta Soni; Akanksha Solanki; Puneet Pareek; Rakesh Kumar Vyas; Sumanta Manna; Sanjib Gayen (Asian Pacific Journal of Cancer Care, 2021)
Purpose: To build safe environment for cancer fighters and radiation personnel during COVID-19 pandemic by focusing on infection control, workflow and radiotherapy dose schedules modification strategies in radiation oncology departments. Material and Methods: A meeting was called post lock down in radiation oncology department to prepare infection control policies and workflow strategies in time of COVID-19 Pandemic. Results: Strategies and policies were formed during COVID-19 crises taking following points into consideration 1) Infection control policies 2) CT simulation policies 3) Day care admission and chemotherapy administration policies 4) Radiation treatment plan modification and delivery strategies 5) Brachytherapy delivery strategies. Conclusion: Management of cancer patients is an issue running parallel to the present condition of COVID-19 pandemic. Further randomized trial on hypofractionated radiotherapy schedules should be encouraged. Positivity, awareness and systematic approach are most important step in balancing the current scenario.